Experiencing school mathematics : traditional and reform approaches to teaching and their impact on student learning - Boaler, Jo, 1964- (Studies in mathematical thinking and learning., 2002)
NORTH AMERICAN RIGHTS ONLY: This is a revised edition of Experiencing School Mathematics first published in 1997 by Open University Press, © Jo Boaler. This revised edition is for sale in North America only. The first book to provide direct evidence for the effectiveness of traditional and reform-oriented teaching methods, Experiencing School Mathematics reports on careful and extensive case studies of two schools that taught mathematics in totally different ways. Three hundred students were followed over three years, providing an unusual and important range of data, includin.